Power Electronics and Power Quality - Pinto, José Gabriel Oliveira (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Power quality (PQ) is receiving more and more attention from consumers, distribution system operators, transmission system operators, and other entities related to electrical power systems. As PQ problems have direct implications for business productivity, causing high economic losses, the research and development monitoring technologies and power electronics solutions that ensure the PQ of the power systems are matters of utmost importance. This book is a collection of high quality papers published in the "Power Electronics and Power Quality" Special Issue of the journal Energies. It reflects on the latest investigations and the new trends in this field.